Seroreactivity against Leptospira spp. differs between community cats and privately-owned cats in Hong Kong - Wing Yan Jacqueline Tam; Omid Nekouei; Francesca Rizzo; Lok See Tiffany Cheng; Yan Ru Choi; Megan Staples; Stefan Hobi; Jane Gray; Fiona Woodhouse; Patricia Yi Man Shuen; Ying Fei Chai; Julia A. Beatty; et al. (One Health)
Leptospirosis is a bacterial zoonotic disease of major One Health significance and public health impact globally, with a wide host range including mammals, cetaceans and herpetofauna. This study aimed to determine Leptospira seroprevalence, risk factors for seroreactivity and prevalence of urinary Leptospira shedding among domestic cats in Hong Kong.Microagglutination testing of 22 Leptospira serovars from 20 serogroups was performed on 738 sera from outdoor free-roaming “community” cats (n = 391) and privately-owned (n = 347) cats. Urine from 268 community cats was tested for pathogenic Leptospira DNA by qPCR targeting lipL32. Potential risk factors associated with exposure were assessed using logistic regression.Overall Leptospira seroprevalence was 9.35%. Of 14 serogroups detected, Javanica (4.3%), Djasiman (2.3%) and Australis (1.5%) were most common. Seroreactivity was significantly higher among community (13.3%) than privately-owned cats (4.9%; OR 2.98 [95% CI 1.68–5.25], P < 0.001), especially to Javanica (7.65% of community cats versus 0.58% of privately-owned cats (P < 0.001). Antibody titres to all serogroups ranged from 1:100 to 1:6400 (median 1:200) and were highest for Javanica (median 1:800).Leptospira DNA was detected in urine from 12/268 community cats (4.48%; median load 6.42 × 102 copies/mL urine; range 1.40 × 101–9.63 × 104). One in three seroreactive community cats with paired urine and blood samples had leptospiruria. After adjusting for source, none of breed, sex, neuter status, age, district rodent infestation rate, serum alanine transaminase or creatinine values were associated with seroreactivity.Cats in Hong Kong are exposed to a diversity of Leptospira serogroups and can shed Leptospira silently in urine. The higher seroprevalence among outdoor free-roaming community cats highlights the importance of environmental drivers in leptospirosis transmission and risks of exposure for sympatric human populations. Gloves should be worn when handling feline urine to minimise the risk of zoonotic transmission from subclinically infected cats.